2016
DOI: 10.5194/cp-12-1565-2016
|View full text |Cite
|
Sign up to set email alerts
|

Regional climate signal vs. local noise: a two-dimensional view of water isotopes in Antarctic firn at Kohnen Station, Dronning Maud Land

Abstract: Abstract.In low-accumulation regions, the reliability of δ 18 O-derived temperature signals from ice cores within the Holocene is unclear, primarily due to the small climate changes relative to the intrinsic noise of the isotopic signal. In order to learn about the representativity of single ice cores and to optimise future ice-core-based climate reconstructions, we studied the stable-water isotope composition of firn at Kohnen Station, Dronning Maud Land, Antarctica. Analysing δ 18 O in two 50 m long snow tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 45 publications
6
86
0
Order By: Relevance
“…Still, on the East Antarctic Plateau, a significant seasonal cycle is depicted in the isotopic composition of the precipitation (Fujita and Abe, 2006;Landais et al, 2012;Stenni et al, 2016) and of the surface snow (Touzeau et al, 2016). So far, whether this seasonal cycle is archived or not in buried snow, and thus, whether stacking an array of snow pits permits to increase the signal to noise ratio and depict a climatic record at the seasonal scale from water isotopic signal remain unclear (Ekaykin et al, 2014;Altnau et al, 2015;Münch et al, 2016). 20 Several studies have focused on understanding how is the climatic signal archived in the isotopic composition of snow and ice on the East Antarctic Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Still, on the East Antarctic Plateau, a significant seasonal cycle is depicted in the isotopic composition of the precipitation (Fujita and Abe, 2006;Landais et al, 2012;Stenni et al, 2016) and of the surface snow (Touzeau et al, 2016). So far, whether this seasonal cycle is archived or not in buried snow, and thus, whether stacking an array of snow pits permits to increase the signal to noise ratio and depict a climatic record at the seasonal scale from water isotopic signal remain unclear (Ekaykin et al, 2014;Altnau et al, 2015;Münch et al, 2016). 20 Several studies have focused on understanding how is the climatic signal archived in the isotopic composition of snow and ice on the East Antarctic Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal variations are also imprinted in the snow isotopic composition of high accumulation sites in coastal areas of Antarctica (Morgan, 1985;Masson-Delmotte et al, 2003;Küttel et al, 2012). For low accumulation sites as found on the East Antarctic Plateau, there is no consensus whether ice core records can reveal the climatic signal at resolutions finer than multidecadal (Baroni et al, 2011) or not (Ekaykin et al, 2002;Pol et al, 2014;Münch et al, 2016). Ekaykin et al (2002) analysed multiple pits from Vostok and identified large spatio-temporal variations caused by post-deposition processes 15 associated with surface topography and wind interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Still, on the East Antarctic Plateau, a clear seasonal cycle is depicted in the isotopic composition of the precipitation (Fujita and Abe, 2006;Landais et al, 2012;Stenni et al, 2016) and of the surface snow (Touzeau et al, 2016). So far, whether this seasonal cycle is archived or not in buried snow, and thus, whether stacking an array of snow pits enables us to increase the signal to 20 noise ratio and depict a climatic record at the seasonal scale from water isotopic signal is an important open question (Ekaykin et al, 2014;Altnau et al, 2015;Münch et al, 2016Münch et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the initial precipitation signal is modified by local post-deposition processes (Ekaykin et al 2002) due to snow-air interactions, such as the impact of metamorphism, wind and surface roughness, and diffusion. It prevents proper recording of the signal at the intra-seasonal and seasonal scale for sites with accumulation lower than 8 cm ice equivalent per year (Münch et al 2016).…”
Section: Resolution and Noisementioning
confidence: 99%